Ultimate guide to business writing : discover all the secrets of creating and managing business documents - Maynard-Smith, Julian (Oxon: Routledge, 2021)
"The Ultimate Guide to Business Writing is a comprehensive guide on how to write any kind of business document. Written clearly in an engaging voice, it explains in depth the whole process: from determining objectives to establishing readers' needs, conducting research, outlining, and designing a template; to writing the first draft; to editing for meaning, accuracy, concision, style and emotional impact; to creating glossaries and indices; to proofreading and working with reviewers. The book also explains how to exploit the psychology of perception and motivation, collaborate effectively with business colleagues, manage documents holistically across an organisation, and deal with the other everyday practicalities of managing knowledge in a corporate environment. Every section of the book is packed with questions to help readers frame their thinking and find the right answers, and dozens of examples of what works and why. The book's also rich in practical examples drawn from real life, anecdotes, humour, and visual aids. But the advice isn't just practical and anecdotal: it's also rigorously supported by scientific evidence from notable linguists and psychologists such as Steven Pinker, Daniel Goleman and Yellowlees Douglas. And anyone keen to explore further will benefit from the book's bibliography and links to videos and other online resources. The book is ideal not just for professional business writers, such as editors, technical writers and communicators, copywriters and creative directors; it's also suitable for anyone whose job requires them to write, whether it's something as simple as an email or as complex as a set of policies or a handbook"--
Includes bibliographical references and index.
Keywords: Business writing. -- Business letters